PENERAPAN BEADING EMBROIDERY DENGAN KOMBINASI CABOCHON TECHNIQUE SEBAGAI HIASAN PADA EVENING GOWN - Sumardani, Pipin Tresna P., Sona (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2021)
Evening gown is one type of party dress that is divided according to the time of use, namely late afternoon or late evening. Evening gowns usually have more prominent characteristics than other types of party dress. Both of the model and decoration/garniture. The application of beads as an evening gown decoration is one way to impress a luxurious impression of evening party dress. Beads or in English called